Channel estimation of UFMC system in multipath channel - Xiang YU; Yanni GAO; Sirui DUAN (Dianxin kexue)
As a candidate waveform of 5G,universal filter multi-carrier (UFMC) technology could inhibit out-of-band radiation,achieve loose synchronization and well support the short bursts of things in the transmission.However,in the UFMC transmission without cyclic prefix (CP),inter-symbol interference (ISI) and subcarrier interference (ICI) are generated in the multipath fading channel,which will affect the estimation accuracy in channel estimation.The interference of the UFMC system in multipath channel was firstly analyzed.After using the feedback equalization suppression ISI,the self-elimination algorithm was used to suppress the ICI according to the similarity between adjacent carriers,and the pilot coefficients were designed according to the UFMC system.Finally,the simulation results show that the proposed method applied to the UFMC can suppress the interference,improve the accuracy and reduce the bit error rate.